2008
DOI: 10.5194/acpd-8-6683-2008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First atmospheric observations of three chlorofluorocarbons

Abstract: Abstract. We report the first atmospheric observations of the Chlorofluorocarbons (CFCs) trifluorochloroethene, 3-chloropentafluoropropene and 4,4-dichlorohexafluoro-1-butene by means of Gas Chromatography with Electron Capture and Mass Spectrometric detection (GC-ECD-MS) in air samples taken at the Taunus Observatory operated by the University of Frankfurt (Main) and the Jungfraujoch High Altitude Research Station in Switzerland. These substances belong to a class of CFCs containing a double bond and are susp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…2. The GC QP MS system was characterised and used before for studies by Laube and Engel (2008);Brinckmann et al (2012) and showed consistent results in the international comparison IHALACE (International Halocarbons in Air Comparison Experiment) with the NOAA (National Oceanic and Atmospheric Administration) network (Hall et al, 2013). We discuss the use of TOF MS in atmospheric trace gas measurements, in particular for the detection and quantification of halocarbons, focusing on four substances: CFC-11, CFC-12, Halon-1211 and Iodomethane.…”
Section: J Hoker Et Al: Comparison Of Gc/time-of-flight Ms With Gc/mentioning
confidence: 98%
“…2. The GC QP MS system was characterised and used before for studies by Laube and Engel (2008);Brinckmann et al (2012) and showed consistent results in the international comparison IHALACE (International Halocarbons in Air Comparison Experiment) with the NOAA (National Oceanic and Atmospheric Administration) network (Hall et al, 2013). We discuss the use of TOF MS in atmospheric trace gas measurements, in particular for the detection and quantification of halocarbons, focusing on four substances: CFC-11, CFC-12, Halon-1211 and Iodomethane.…”
Section: J Hoker Et Al: Comparison Of Gc/time-of-flight Ms With Gc/mentioning
confidence: 98%
“…The corrected relative sensitivity is then given by the relative sensitivity divided by the fragmentation factor. The methodology is derived and explained in more detail in [26]. To test the validity of this approach, we tested the predictability of mixing ratios for two other recently-calibrated CFC isomer pairs: CFC-112/CFC-112a and CFC-113/CFC-113a [25].…”
Section: Calibrationmentioning
confidence: 99%
“…For quality assurance of the laboratory instrumentation, five air samples were analysed and compared to our reference GC-QPMS (gas chromatograph coupled to a quadrupole mass spectrometer) which uses a similar preconcentration setup (Hoker et al, 2015). Consistent results with the NOAA network (National Oceanic and Atmospheric Administration) were demonstrated for the GC-QPMS in the past during the IHALACE intercomparison (Hall et al, 2014), however with a different sample preconcentration using liquid nitrogen (Brinckmann et al, 2012;Laube and Engel, 2008;Laube et al, 2010). The current laboratory setup using the Stirling cooler-based preconcentration has been described by Hoker et al (2015) and has shown very consistent results with previous measurements.…”
Section: Laboratory Operation: Flask Sample Measurementsmentioning
confidence: 86%